(untitled) (Business Vision, 2020)
The lubricating oils used come from the fractional refining of petroleum, in their useful life they have many uses and the main one is the lubricants of the automotive sector, once this life cycle ends this hydrocarbon becomes a waste difficult to undo and with a high degree of contamination since in its final composition this oil has particles of lead, cadmium, arsenic, chlorine etc that are highly polluting chemicals for our environment and water sources, study show that when this oil is burned it releases more lead to the atmosphere q any other source of pollution and when it is thrown into water sources a single liter can contaminate a thousand liters of water making this that can not be drunk. In the city of San Juan de Pasto there is no entity responsible for collecting this oil periodically, store it, treat it, filter it and reincorporate it into the market, as there is no system to take care of all this, it becomes a difficult waste to undo for all servitecas facilitating the illegal trade of this hydrocarbon for combustion in different activities as it is very economical, but harmful to health and the environment